Improving Sensorimotor of Children With Intellectual Disability Through Teaching Writing in Shanti Yoga Special School, Klaten Central Java - Tias Martika (The Center for Disability Studies and Services Brawijaya University, 2020)
The present study aimed to improve sensorimotor skills of children with intellectual disability through writing. The subjects of the study were fifteen fifth-grade students with intellectual disability in Shanti Yoga Special School, Klaten. The present study employed experimental method with one group pretest-posttest design.The subjects were treated in a certain amount of times, the effects were measured from the difference gained between pretest and posttest result. Due to limited number of students, the researcher could not do sampling. Accordingly, the researchers involved all individuals in population (total sampling). The data were collected using essay test in order to measure their initial writing skills. The instrument was considered valid by three experts in terms of content, construct, and language. The present study employed non-parametric statistic analysis method, Wilcoxon Signed Rank Test, this was done using SPSS 20. The descriptive analysis result showed the average posttest score was 12.93, which was greater than the pretest score (11.60). Non-parametric analysis found the z-value of -2.83 with asymp. Sig. (2-tailed) = 0.022, accordingly, hypothesis stating that there is a significant effect on the improvement of sensorimotor of children with intellectual disability through teaching writing was accepted. This study concludes that there is an effective improvement of sensorimotor of children with intellectual disability through writing learning process in SLB Shanti Yoga Klaten.